Penggunaan Calistung untuk Meningkatkan Literasi Numerasi Peserta Didik Kelas 2 - Deiby Kolamban; Juliana Margareta Sumilat; Deysti Trifena Tarusu (Peneliti.net, 2023)
Calistung's definition includes reading, writing and arithmetic skills. Implementation of Calistung should be carried out at the basic education level to strengthen students' literacy and numeracy skills. However, some students at this level still face important challenges in the competency aspects of reading, writing and arithmetic. Therefore, it is crucial to design learning programs that adopt innovative approaches to improve students' literacy and numeracy skills. This research aims to describe how Calistung is implemented, while identifying barriers and finding solutions for instructors when guiding students with difficulties in literacy and numeracy. The data validation process will integrate resources and procedures through a triangulation approach, including observation, interviews and documentation methods. From the research results, it was found that teachers spent additional time implementing the Calistung program for students. The calistung program is often used with various reading materials, letter and number cards, as well as contextual learning techniques. The instructor then distributes books that the children want to read and introduces numbers by performing simple arithmetic operations.